The Relationship between Land-lost Farmers and Local Government in China : Integration, Conflict, and Their Interplay - Lian, Hongping (Springer Singapore : Imprint: Springer, 2017)
The study is set against the backdrop of the urbanization trend in present-day China, and focuses on the relationship between farmers who have lost their land ("land-lost farmers") and local government. Particularly, it applies the extended case method to answer the following two questions: first, in what ways do the forces of integration and conflict manifest themselves in the relationship between land-lost farmers and local government? Second, how do land-lost farmers and local government apply respective modalities in the context of their interplay? The main finding is that the two groups, land-lost farmers and officials, are engaged in a complex and dynamic relationship. That relationship is played out locally within a network of power-interest structures, which not only manifests itself as forces of integration and conflict, but also as an ongoing process, a game played by knowledgeable agents, whose strategies are enacted, and in so doing, both reproduce that game and alter it. Readers will gain an ethnographic understanding of the relationship based on an in-depth examination of perspectives on both sides of the equation.
Keywords: Social sciences.; Urban geography.; Ethnology.; Political sociology.; elektronické knihy; electronic books